The influence of e-commerce, information systems and entrepreneurial knowledge in decision making on student interest in entrepreneurship - Panggabean, Berliana Febrianti; Nikmah, Nikmah (Institute of Computer Science (IOCS), 2023)
In the current technological era, almost everything can be accessed easily and quickly. One form of information technology that is currently developing is electronic commerce (e-commerce), the use of information systems and entrepreneurial knowledge. It will be easier for an entrepreneur to run his business if he understands the accounting information system that can be used in making decisions so that the business he runs can continue to survive. This research aims to examine the influence of e-commerce, information systems and entrepreneurial knowledge in making entrepreneurial decisions among students at several universities, high schools and polytechnics in the city of Bengkulu. Determining the sample in this research uses a purposive sampling technique, namely a technique for determining the sample using certain considerations. The number of respondents used in this research was 210 people. The research method used is quantitative research and for data analysis using multiple linear regression analysis. The results of this research state that e-commerce has a positive influence on entrepreneurial decision making, information systems have a positive influence on entrepreneurial decisions, and entrepreneurial knowledge has a positive influence on entrepreneurial decisions